ANALISIS PREDIKSI POTENSI KEBANGKRUTAN PADA PT BANK MUAMALAT INDONESIA Tbk PERIODE 2012-2016 DENGAN MENGGUNAKAN METODE ALTMAN MODIFIKASI - Dewi Laela Hilyatin (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2017)
Abstract Bankruptcy is a very essential issue that every company should be aware of. Bankruptcy of a company can be minimized by advanced prediction; such as analyzing the financial statements. This study discusses the financial performance of PT Bank Muamalat Indonesia Tbk, which indicates that there is a degression in some number of financial ratios, the closing of offices and firing of employees in 2012-2016, causing he fact that BMI must pay attention and improve its financial performance and anticipate the existence of a bankruptcy in the company. Based on Altman analysis modification for financial performance of PT Bank Muamalat Indonesia Tbk in 2012-2016, it found Z-Score value of 0,825, 0,659, 1,243, 0,982 and 0,892. Based on Z-Score criteria, PT Bank Muamalat Indonesia Tbk is predicted to experience problems in management and financial structure and also in potentially bankruptcy due to Z-Score value <1,1 while the highest Z-Score value is in 2014, which shows the value of Z-Score>1,1 and <2,6, which means the company is in the gray area, meaning the company’s category is not said to be bankrupt and also not healthy. Keywords: Bankruptcy, Altman Modification Method